2015
DOI: 10.1007/s13318-015-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Curcumin Diethyl Disuccinate, a Prodrug of Curcumin, in Wistar Rats

Abstract: Curcumin diethyl disuccinate did not significantly improve the oral bioavailability of curcumin due to first pass metabolism in the gastrointestinal tract. Further studies on reduction of first pass metabolism are required to optimise delivery of curcumin using a prodrug approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…8 In addition, a previous pharmacokinetic study of CDD in rats showed that CDD has superior tissue distribution in comparison with CUR. 9 The data implied that CDD enhanced the oral bioavailability of CUR since both compounds were orally administered at the dose of 40 mg kg À1 while CDD has a molecular weight 1.7 times higher than CUR (MW 624 vs. 368, respectively). Therefore, CDD is a promising ester prodrug of CUR for further development as a drug candidate.…”
Section: Introductionmentioning
confidence: 97%
“…8 In addition, a previous pharmacokinetic study of CDD in rats showed that CDD has superior tissue distribution in comparison with CUR. 9 The data implied that CDD enhanced the oral bioavailability of CUR since both compounds were orally administered at the dose of 40 mg kg À1 while CDD has a molecular weight 1.7 times higher than CUR (MW 624 vs. 368, respectively). Therefore, CDD is a promising ester prodrug of CUR for further development as a drug candidate.…”
Section: Introductionmentioning
confidence: 97%
“…Owing to its diverse biological activities and low toxicity, curcumin is an attractive compound for drug development (Strimpakos and Sharma, 2008;Pouliquen, 2014;Ratnatilaka Na Bhuket et al, 2017;Pagano et al, 2018;Rafiee et al, 2019). However, its poor water solubility, chemical and metabolic instability, and low bioavailability pose challenges in its application as a therapeutic agent (Anand et al, 2007;Bangphumi et al, 2016;Toden and Goel, 2017;Dei Cas and Ghidoni, 2019). To overcome these barriers, curcumin has been formulated or covalently designed in the form of nanoparticles (Boonyasirisri et al, 2015;Luckanagul et al, 2018;Gomez et al, 2019), polymer conjugates (Wichitnithad et al, 2011a), and prodrugs (Wichitnithad et al, 2011b;Muangnoi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further processing of CDD in chitosan-alginate nanoparticles sustains its release for at least 72 h, with enhanced cellular uptake and cytotoxicity in human breast adenocarcinoma (MDA-MB-231) cells (Bhunchu et al, 2015;Bhunchu et al, 2016;Sorasitthiyanukarn et al, 2017). The pharmacokinetics of CDD in rats showed that CDD is rapidly eliminated from the bloodstream following oral and intravenous administration via plasma esterase hydrolysis (Bangphumi et al, 2016). Further, in vitro plasma metabolism studies have shown that CDD is rapidly converted to curcumin in the plasma of rats, dogs, and humans, with different hydrolytic rates and various plasma esterases involved (Ratnatilaka Na Bhuket et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The human liver and gut microsomes treated with 20 µM curcumin form glucuronides of curcumin and its phase I metabolites [11]. It is very difficult to model human metabolism accurately in animals, but rat mucosa metabolises curcumin [12] and the major metabolites in male rats gavaged with curcumin (Meriva; 340 mg/kg (curcumin) and euthanized 20 min afterwards) were also glucuronides of curcumin and desmethoxycurcumin, with some evidence for reduction [13]. Even if administered intraperitoneally, lipophilic substances, such as curcumin, will drain into the hepatic portal vein for transport to liver and metabolism, prior to distribution around the body [14].…”
Section: Introduction: the Need To Protect Curcumin In The Bodymentioning
confidence: 99%